The Impact of Instagram Social Media Utilization on Sales Revenue of MSMEs Products in the Digital Era - Tarso; Saputra, Yohan Dwi; Siswanto, Deny Hadi (Journal of Management Studies and Development, 2025)
This study aims to examine the impact of social media on increasing sales in Micro, Small, and Medium Enterprises (MSMEs) in the Kapanewon Kalasan, Sleman Regency. The type of research used is correlational research with a descriptive quantitative approach and simple linear regression analysis technique. This research was conducted in November 2024, with 33 subjects selected using incidental sampling. Simple regression analysis was used to test the effect of Instagram social media (X) on sales revenue (Y). The analysis techniques used include validity testing, reliability testing, normality testing, linearity testing, and determination testing. The results show that Instagram social media has an impact on sales revenue in the MSMEs of Forkom Kapanewon Kalasan, with an R-value of 0.552, or 55.2%, indicating a high level of influence.